Can low-carbon transformation enhance ecological resilience?——Evidence from China’s low-carbon city pilot policy - Song, Zhida; Wang, Li (Frontiers in Environmental Science, 2025)
In the context of increasing global uncertainty and climate-related challenges, low carbon transformation is crucial for China to achieve its “carbon peak and carbon neutrality” objectives. This initiative also serves as a vital approach to bolster ecological capacity and maintain ecosystem stability. This study aims to systematically evaluate the policy effects of LCC pilot initiatives on enhancing urban ecological resilience, thereby providing scientific evidence for refining low-carbon development policies. To this end, the research employs a difference-in-differences (DID) model to examine the effects of low carbon transformation on ecological resilience (ERS) from 2005 to 2022, utilizing China’s LCC pilot policies as a quasi-natural experiment. The findings indicate that the low carbon transformation markedly enhances ERS, with this conclusion holding strong across multiple assessments. Mechanistic analysis further reveals that LCC construction enhances ERS by promoting industrial restructuring and upgrading of industrial structure (UIS), as well as reducing energy consumption intensity (ECI). Additionally, government-enforced environmental regulations (ERGs) act as an external force, amplifying the positive effects of LCC pilot initiatives on ERS. This study is the first to systematically examine the impact mechanisms of LCC pilot policies on ERS, filling a critical gap in policy evaluation and urban sustainable development research. The findings not only provide empirical evidence for low-carbon city construction but also offer important insights for policy optimization in global urban green transitions.